Challenging Axillary Lymph Nodes on PET/CT in Cancer Patients throughout COVID-19 Vaccination Era - Giordano, Alessia; Gallicchio, Rosj; Milella, Mariarita; Storto, Rebecca; Nardelli, Anna; Pellegrino, Teresa; Nappi, Antonio; Di Cosola, Michele; Storto, Giovanni (Current Pharmaceutical Design, 2024)
Background: The unexpected detection of axillary lymphadenopathy (AxL) in cancer patients (pts) represents a real concern during the COVID-19 vaccination era. Benign reactions may take place after vaccine inoculation, which can mislead image interpretation in patients undergoing F-18-FDG, F-18-Choline, and Ga-68-DOTATOC PET/CT. They may also mimic loco-regional metastases or disease. We assessed PET/CT findings after COVID-19 first dose vaccination in cancer patients and the impact on their disease course management. Methods: We evaluated 333 patients undergoing PET/CT (257 F-18-FDG, 54 F-18-Choline, and 23 Ga-68 DOTATOC) scans after the first vaccination with mRNA vaccine (Pfizer-BioNTech) (study group; SG). The uptake index (SUVmax) of suspected AxL was defined as significant when the ratio was > 1.5 as compared to the contralateral lymph nodes. Besides, co-registered CT (Co-CT) features of target lymph nodes were evaluated. Nodes with aggregate imaging positivity were further investigated. Results: Overall, the prevalence of apparently positive lymph nodes on PET scans was 17.1% during the vaccination period. 107 pts of the same setting, who had undergone PET/CT before the COVID-19 pandemic, represented the control group (CG). Only 3 patients of CG showed reactive lymph nodes with a prevalence of 2.8% (p < 0.001 as compared to the vaccination period). 84.2% of SG patients exhibited benign characteristics on co-CT images and only 9 pts needed thorough appraisal. Conclusion: The correct interpretation of images is crucial to avoid unnecessary treatments and invasive procedures in vaccinated cancer pts. A detailed anamnestic interview and the analysis of lymph nodes’ CT characteristics, after performing PET/CT, may help to clear any misleading diagnosis.
Keywords: COVID-19